A Review of Plant-Mediated and Fertilization-Induced Shifts in Ammonia Oxidizers: Implications for Nitrogen Cycling in Agroecosystems - Durga P. M. Chinthalapudi; William Kingery; Shankar Ganapathi Shanmugam (Land)
Nitrogen (N) cycling in agroecosystems is a complex process regulated by both biological and agronomic factors, with ammonia-oxidizing archaea (AOA) and bacteria (AOB) playing pivotal roles in nitrification. Despite extensive fertilizer applications to achieve maximum crop yields, nitrogen use efficiency (NUE) remains less than ideal, with substantial losses contributing to environmental degradation. This review synthesizes current knowledge on plant-mediated and fertilization-induced shifts in ammonia-oxidizer communities and their implications on nitrogen cycling. We highlight the differential ecological niches of AOA and AOB, emphasizing their responses to plant community composition, root exudates, and allelopathic compounds. Fertilization regimes of inorganic nitrogen inputs and biological nitrification inhibition (BNI) are examined in the context of microbial adaptation and ammonia tolerance. Our review highlights the need for integrated nitrogen management strategies comprising optimized fertilization timing, nitrification inhibitors, and plant–microbe interactions in order to optimize NUE and mitigate nitrogen losses. Future research directions must involve applications of metagenomic and isotopic tracing techniques to unravel the mechanistic AOA and AOB pathways that are involved in regulating these dynamics. An improved understanding of these microbial interactions will inform the creation of more sustainable agricultural systems that aim to optimize nitrogen retention and reduce environmental footprint.